CPAP IMPACT: a protocol for a randomised trial of bubble continuous positive airway pressure versus standard care for high-risk children with severe pneumonia using adaptive design methods. Issue 1 (30th June 2017) - Smith, Andrew G; Eckerle, Michelle; Mvalo, Tisungane; Weir, Brian; Martinson, Francis; Chalira, Alfred; Lufesi, Norman; Mofolo, Innocent; Hosseinipour, Mina; McCollum, Eric D
Abstract : Introduction: Pneumonia is a leading cause of mortality among children in low-resource settings. Mortality is greatest among children with high-risk conditions including HIV infection or exposure, severe malnutrition and/or severe hypoxaemia. WHO treatment recommendations include low-flow oxygen for children with severe pneumonia. Bubble continuous positive airway pressure (bCPAP) is a non-invasive support modality that provides positive end-expiratory pressure and oxygen. bCPAP is effective in the treatment of neonates in low-resource settings; its efficacy is unknown for high-risk children with severe pneumonia in low-resource settings. Methods and analysis: CPAP IMPACT is a randomised clinical trial comparing bCPAP to low-flow oxygen in the treatment of severe pneumonia among high-risk children 1–59 months of age. High-risk children are stratified into two subgroups: (1) HIV infection or exposure and/or severe malnutrition; (2) severe hypoxaemia. The trial is being conducted in a Malawi district hospital and will enrol 900 participants. The primary outcome is in-hospital mortality rate of children treated with standard care as compared with bCPAP. Ethics and dissemination: CPAP IMPACT has approval from the Institutional Review Boards of all investigators. An urgent need exists to determine whether bCPAP decreases mortality among high-risk children with severe pneumonia to inform resource utilisation in low-resource settings. Trial registration number: NCT02484183; Pre-results.